Telemedicine Implementation and Digital Health Innovation: An Empirical Study in Healthcare Services - Mochamad Malik Akbar Rohandi; Putri Fariska; Qonidah Salsabila Senja (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid development of digital technologies has encouraged healthcare organizations to adopt telemedicine as part of digital health innovation to improve healthcare service management. However, the effectiveness of telemedicine implementation in supporting healthcare service performance remains a critical issue in many healthcare institutions. This study examines the relationship between telemedicine implementation and digital health innovation in improving healthcare service performance. The research applies a quantitative empirical approach using a survey method involving 180 healthcare professionals working in hospitals and healthcare facilities in Bandung, Indonesia. Respondents were selected using purposive sampling based on their experience with telemedicine systems. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The findings show that telemedicine implementation has a positive and significant effect on digital health innovation and contributes to improving service efficiency, communication quality, and patient management processes in healthcare services. The study also indicates that integrating telemedicine technologies strengthens healthcare organizations’ capacity to deliver more responsive and technology-driven services. These findings highlight the importance of telemedicine as a strategic tool for supporting digital transformation and improving healthcare service management.